Serum insulin-like growth factor-1 and insulin-like growth factor binding protein-3 levels in patients with chronic hepatitis B - HAKLAR, GONCAGÜL (WALTER DE GRUYTER GMBH, 2016)
Objective: Decreased serum insulin-like growth factor-1 (IGF-1) and insulin like growth factor binding protein-3 (IGFBP-3) levels have been found in patients with chronic liver disease of different etiologies, but these factors have not been studied extensively in patients with hepatitis B virus (HBV)-induced chronic liver disease. Methods: We have investigated serum IGF-1 and IGFBP-3 levels in 40 patients with chronic HBV and 40 patients with HBV-induced cirrhosis. According to Child-Pugh classification cirrhotic patients were divided into three groups. Forty age-and sex-matched healthy subjects served as controls. IGF-1 and IGFBP-3 levels were measured by immunochemiluminescence. The results were compared with those for serum albumin, total bilirubin, transaminase activity, and with prothrombin time. Results: IGF-1 and IGFBP-3 levels were significantly lower in patients with cirrhosis than in those with chronic HBV and in controls (p<0.001). In chronic HBV patients, IGFBP-3 levels were significantly lower than in controls (p=0.013). IGF-1 and IGFBP-3 levels were significantly lower in cirrhotic patients with Child-Pugh stage B and Child-Pugh stage C compared with Child-Pugh stage A (for IGF-1 p=0.037 and p<0.001, for IGFBP-3 p=0.036 and p<0.001, respectively). In patients with Child-Pugh stage C significantly IGF-1 levels were lower than in patients with Child-Pugh stage B (p=0.003). IGF-1 and IGFBP-3 levels were positively correlated with serum albumin concentrations and negatively correlated with serum total bilirubin and prothrombin time concentrations in cirrhotic patients. IGF-1 and IGFBP-3 levels in chronic HBV patients were negatively correlated with serum transaminases. Conclusion: We conclude that serum levels of IGF-1 and IGFBP-3 may be useful markers for liver dysfunction in patients with HBV-induced chronic liver disease.
Keywords: IGF-1; IGFBP-3; cirrhosis; HBV; LIVER-CIRRHOSIS; IGF-I; TERNARY COMPLEX; HORMONE; IGFBP-3; DYSFUNCTION; EXPRESSION; PROGNOSIS; INFECTION; DISEASE